Non-alcoholic Fatty Liver Disease as a Canonical Example of Metabolic Inflammatory-Based Liver Disease Showing a Sex-Specific Prevalence: Relevance of Estrogen Signaling - Della Torre, Sara (Frontiers in Endocrinology, 2020)
There is extensive evidence supporting the interplay between metabolism and immune response, that have evolved in close relationship, sharing regulatory molecules and signaling systems, to support biological functions. Nowadays, the disruption of this interaction in the context of obesity and overnutrition underlies the increasing incidence of many inflammatory-based metabolic diseases, even in a sex-specific fashion. During evolution, the interplay between metabolism and reproduction has reached a degree of complexity particularly high in female mammals, likely to ensure reproduction only under favorable conditions. Several factors may account for differences in the incidence and progression of inflammatory-based metabolic diseases between females and males, thus contributing to age-related disease development and difference in life expectancy between the two sexes. Among these factors, estrogens, acting mainly through Estrogen Receptors (ERs), have been reported to regulate several metabolic pathways and inflammatory processes particularly in the liver, the metabolic organ showing the highest degree of sexual dimorphism. This review aims to investigate on the interaction between metabolism and inflammation in the liver, focusing on the relevance of estrogen signaling in counteracting the development and progression of non-alcoholic fatty liver disease (NAFLD), a canonical example of metabolic inflammatory-based liver disease showing a sex-specific prevalence. Understanding the role of estrogens/ERs in the regulation of hepatic metabolism and inflammation may provide the basis for the development of sex-specific therapeutic strategies for the management of such an inflammatory-based metabolic disease and its cardio-metabolic consequences.